Expression of guanylate cyclase C in human prefrontal cortex depends on sex and feeding status - Ratko, Martina; Crljen, Vladiana; Tkalčić, Martina; Mažuranić, Anton; Bubalo, Pero; Škavić, Petar; Banovac, Ivan; Dugandžić, Aleksandra (Frontiers in Molecular Neuroscience, 2024)
Guanylate cyclase C (GC-C) has been detected in the rodent brain in neurons of the cerebral cortex, amygdala, midbrain, hypothalamus and cerebellum. In this study we determined GC-C protein expression in Brodmann areas (BA) 9, BA10, BA11 and BA32 of the human prefrontal cortex involved in regulation of feeding behaviour, as well as in the cerebellar cortex, arcuate nucleus of hypothalamus and substantia nigra in brain samples of human 21 male and 13 female brains by ELISA with postmortem delay less than 24h. GC-C was found in all tested brain areas and it was expressed in neurons of the third cortical layer of BA9. The regulation of GC-C expression by feeding was found in male BA11 and BA10-M, where GC-C expression was in negative correlation to the volume of stomach content during autopsy. In female BA11 there was no correlation detected, while in BA10-M there was even positive correlation. This suggests sex differences in GC-C expression regulation in BA11 and BA10-M. The amount of GC-C was higher in female BA9 only when the death occurred shortly after a meal, while expression of GC-C was higher in BA10-O only when the stomach was empty. The expression of GC-C in female hypothalamus was lower when compared to male hypothalamus only when the stomach was full, suggesting possibly lower satiety effects of GC-C agonists in women. These results point towards the possible role of GC-C in regulation of feeding behavior. Since, this is first study of GC-C regulation and its possible function in prefrontal cortex, to determine exact role of GC-C in different region of prefrontal cortex, especially in humans, need further studies.